Financování projektu z fondů EU - Veselý, Jiří (Vysoké učení technické v Brně. Fakulta podnikatelská, 2011)
Diplomová práce se zaměřuje na vytvoření projektové žádosti pro organizaci AIESEC Česká republika, která odpovídá požadavkům na čerpání finančních prostředků z fondů Evropské unie.

The diploma thesis focuses on creating of a project documentation for organization AIESEC Czech Republic that is in compliance with requirements of the European Union to use financial resources from European funds.
Project Financing from the EU Funds
Keywords: Projekt; fond; rozpočet; žádost; aktivita; Evropský sociální fond; způsobilé náklady; státní rozpočet; operační program; Project; fund; budget; application; activity; European Social Fund; eligible costs; state budget; operational programme